KINERJA APARATUR KECAMATAN TIKALA DALAM MEWUJUDKAN MANADO KOTA YANG BERSIH DI KECAMATAN TIKALA KOTA MANADO PROVINSI SULAWESI UTARA - Udaya Madjid; Abdulrokhman Pratama (Jurnal Media Birokrasi, 2021)
Creating a "clean" Manado through improving the performance of waste management services from the Manado city environmental department has been decentralized to every district in its working area. The performance of the sub-district apparatus needs to be optimized in realizing the goals of the Manado City government. The obstacles to realizing Manado City that are clean are found in the recall of the performance of the sub-district apparatuses, the enforcement of regional regulations and the guidance of the government to the community in order to live cleanly. Therefore, the researcher is interested in measuring the performance of the Tikala District apparatus in realizing Manado a clean city. In solving problems researchers use the theory of performance according to Agus Dwiyanto with descriptive qualitative research designs through an inductive approach. The techniques used in data collection are interviews, observation, and documentation. Data analysis techniques include data reduction, data display, and conclusions or verification. The results of the research conducted by researchers showed the ineffectiveness of the performance of the sub-district apparatus, because they did not meet several indicators, namely in terms of achieving the target, there were still many numbers of janitors not proportional to the area of the sub-district, which caused sub-optimal performance of employees in carrying out a job. Dissemination of local regulations is still lacking so that the community is still difficult to regulate in independent waste management. The amount of waste that is always increasing every month requires effective handling by the government and cleaning infrastructure that requires a large amount of money and time that is not small in its procurement. The researcher concludes that the performance of the subdistrict apparatus has not been able to achieve what is the goal of the Tikala District in realizing a clean subdistrict area. Researchers suggest that Tikala sub-district is to improve the quality of work of both subdistrict employees and casual daily laborers. Improving waste management infrastructure and the need for close supervision of waste laws. The awareness of Tikala Subdistrict community must also be increased by providing counseling about waste. There should be cooperation between the community and the government in handling the waste problem. Keywords: Performance, Apparatus